Peran Pengalokasian Dana Tepat dan Pendampingan dari Fasilitator Bagi Usaha Nasabah Prasejahtera Produktif BTPN Syariah Wilayah Kebonagung - Dhea Fitri Puspitayani; Budi Prabowo (Economic Reviews Journal, 2025)
The UMKM empowerment program initiated by BTPN Syariah in partnership with MSIB aims to enhance the capacity of micro-enterprises owned by productive underprivileged clients, particularly women entrepreneurs in rural areas. The core components of this program include financing and funding, optimized through mentoring facilitators under the BESTEE (Sahabat Daya) program. This mentoring process consists of four stages: assessment, material delivery, review and practice, and the presentation of outcomes. In the assessment stage, an analysis of business potential and challenges is conducted, including the identification of marketing problems and a SWOT analysis. The educational materials provided in the second stage focus on business development solutions, such as branding, business identity, and digital marketing. The review and practice stage ensures the clients’ understanding and application of the material. In the final meeting, the outcomes of the mentoring process, such as marketing tools like banners or social media accounts, are handed over to support business development. The program's results indicate an increase in the economic value of clients' micro-enterprises through effective mentoring and practical education. This collaboration between BTPN Syariah and MSIB is expected to help clients overcome business challenges, utilize funding assistance, and compete in the global era. This program serves as an integrated and sustainable empowerment model for local MSME development.